ANALISIS HUBUNGAN FAKTOR DEMOGRAFI, PELATIHAN DAN PENGEMBANGAN DENGAN KINERJA PEGAWAI (Studi Pada Badan Pusat Statistik Kabupaten Kapuas, Kalimantan Tengah). - Rephy Ekawatie; Ahmad Alim Bachri (JWM (JURNAL WAWASAN MANAJEMEN), 2014)
This study aimed to analyze the relationship between demographic factors, training and developing the performance of employees in BPS Kapuas District of Central Kalimantan. This research is a quantitative study menggunakam testing methods Spearman Rank Order Correlation analysis of the overall employee population BPS Kapuas totaling 22 people. The results showed that partially each variable X (Demographic factors (X1), Training (X2) and Development (X3)) positively and significantly related to performance (Y). The relationship of each variable X (Factor Demographics, Training and Development) simultaneously be in a very strong category with a variable Y (Performance). Among the tested three variables X, Development variable (X3) have the Spearman Rank correlation coefficient greatest